Between Thin- and Host-ideologies: How Populist Attitudes Interact with Policy Preferences in Shaping Voting Behaviour. Issue 4 (2nd October 2019) - Loew, Nicole; Faas, Thorsten
ABSTRACT: Understanding populism as a thin-centred ideology implies that it is in need for a host ideology in order to be successful. In addition to being populist, populist parties have to give substantial, policy-related answers to political problems. Even though this twofold structure is an often-debated topic in theory, there is rather little attention payed to the question of how this relationship affects voting behaviour. Using Germany after the 2017 general election as a case, we want to study the demand side of populism and focus on the voters of the Alternative für Deutschland (Alternative for Germany, AfD) and Die Linke (Left Party). Comparing voters of a populist radical right and left party enables us to find out more about the interaction of populist attitudes and policy preferences at the individual level and how they affect electoral behaviour.